2013
DOI: 10.1111/jai.12212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of boiling, deep-frying, and microwave treatment on the proximate composition of rainbow trout fillets: changes in fatty acids, total protein, and minerals

Abstract: Summary This study was conducted to investigate the differences in the proximate composition (moisture, fat, protein and ash), cholesterol content, energy, mineral composition (Na, Ca, Mg, K, P, Fe and Zn) and fatty acid profile of rainbow trout, Oncorhynchus mykiss, after frying, boiling, or microwaving. Results showed that all cooking methods reduced moisture and increased total protein, fat and ash contents. Also all minerals increased significantly during the microwave and frying methods. Statistical resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
35
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 31 publications
8
35
1
Order By: Relevance
“…Similar results have been found in boiled rainbow trout fillets [38]. On the other hand, some researchers disagree with our findings in case of three commonly consumed marine fishes in Nigeria [39].…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Similar results have been found in boiled rainbow trout fillets [38]. On the other hand, some researchers disagree with our findings in case of three commonly consumed marine fishes in Nigeria [39].…”
Section: Resultssupporting
confidence: 73%
“…This might be due to reduction of moisture content. Increased total protein was also found with reduced rate of moisture content in boiled rainbow trout fillets [38]. …”
Section: Resultsmentioning
confidence: 99%
“…A similar observation was made in the content of protein and minerals upon frying of fish and shrimp by Musaiger and D'Souza (). Asghari et al () also reported that the protein and mineral elements (dry basis) decreased when rainbow trout fillets were subjected to deep‐fat frying. These observations indicate extensive absorption of the frying oil into clams.…”
Section: Resultsmentioning
confidence: 94%
“…Similar to the current study, several researchers observed the decline of FFA content in silver cat fish and anchovy after frying (Turhan et al, ; Weber et al, ). It was suggested that FFA leach out from fried meat and the dilution effects of frying oil accounts for the decrease in AV (Asghari et al, ; Turhan et al, ). Another reason is evaporation assisted by steam during frying.…”
Section: Resultsmentioning
confidence: 99%
“…However, according to the results, the use of MWB allowed a better retention of minerals in mackerel fillets. It is known in the literature that MWB, compared with the conventional heating methods, leads to less leaching of the nutrient, preserving the overall nutritional content of the processed food (Asghari, Zeynali, & Sahari, ; Gómez‐Guillén et al, ). However, different behaviors in the fractional decrease of lipids were observed among the treatments after marinating.…”
Section: Resultsmentioning
confidence: 99%